Pengenalan Mitigasi Bencana Banjir untuk Anak Sekolah Dasar melalui Media Digital Video Pembelajaran - Qoni’ah Al Munasiroh (Educational Journal, 2026)
Floods are on of the natural disaster that often occur in Indonesia. Flood disaster mitigation need to introduced as a precautionary measure to deal with the floods. Disaster mitigation must be given since young age with an easy to understand. This research is a study on the implementation of digital learning video media to introduce flood disaster mitigation to early childhood. This study uses a qualitative approach so that the research results can be described as factually and profound. The subjects of this study were 286 children of junior high school in on of the SDIT Baiturrahman in Sragen. The results of the study indicate that digital media in the form of video can be used as a learning resource to introduce flood disaster mitigation to early childhood. Children understand more about flood disasters and their risk factors after seeing digital learning video media. The development of flood disaster mitigation programs in the form of digital video learning media has been proven to foster knowledge and attitudes of early childhood to respond to disasters from an early age. Implementation of disaster mitigation programs through learning videos has several benefits, including easy access, easy to use, general in nature, and can be used in many places.